Balloon Eustachian Tuboplasty-A Feasible Double-Blinded Sham Surgery Randomized Clinical Trial Protocol to Study Efficacy - Laakso, Juha T (WILEY, 2025)
Introduction: Balloon Eustachian tuboplasty (BET) is used to treat obstructive Eustachian tube dysfunction (OETD) and recurrent otitis media with effusion (OME). However, there are no indisputable evidence of its efficacy. Here, we present a multicenter, double-blinded, randomized, placebo-controlled trial (MDRCT) design to evaluate the efficacy of BET, and the results of a pilot trial with 3- and 12-months' follow-up.
Material and methods: This was a prospective MDRCT. For a pilot study, OETD (n = 10) and OME (n = 5) patients were recruited and followed. Detailed inclusion and exclusion criteria were used. Participants were randomized at beginning of the operation to active or sham surgery. All procedures were performed under local anesthesia. Controls were performed in double-blinded manner (both patient and physician), at 3 and 12 months after the procedure.
Results: Altogether, 20 ears were treated and followed for 12 months, including 14 active BETs and 6 sham surgeries. Both the active and sham surgery were performed under local anesthesia without problems or deviations from the protocol. There were no differences in the preoperative symptoms (ETDQ-7) or objective measures (tympanometry, Valsalva and Toynbee maneuvers, tubomanometry, Eustachian tube score) between active and sham surgery arms. During follow-up, we noticed largely similar reduction in subjective symptoms and improvement in Eustachian tube score both in active and sham surgery arms.
Conclusions: The pilot study demonstrates that our MDRCT protocol is feasible, and that blinded RCTs are dearly needed to objectively measure the efficacy of BET.
Level of evidence: 2 Laryngoscope, 2023.